Reducing Exhaust Emissions from Palm Oil Biodiesel Diesel Engines by Adding Hydrogen Gas - Kuntang Winangun; Yoyok Winardi; Indah Puspitasari; Nanang Suffiadi Akhmad; Rizki Dwi Ardika; Salih Ozer (Universitas Muhammadiyah Magelang, 2024)
The application of hydrogen enrichment of palm oil-based biodiesel in a compression ignition engine was examined in this work. Synthesized from crude palm oil (CPO), biodiesel was first fed into a single-cylinder diesel engine. The intake manifold received hydrogen gas at flows of 2.5 L/min, 5 L/min, 7.5 L/min, and 10 L/min. Operating at a constant speed of 2,000 rpm, the single-cylinder, direct-injection diesel engine used The aim of this work is to assess the performance and emissions of a diesel engine utilizing hydrogen gas and CPO biodiesel fuels. This work examined engine performance and exhaust emissions using smoke emissions, exhaust temperature, power, thermal efficiency, and fuel economy. Addition of hydrogen improved emissions and performance. Optimal engine performance was achieved by adding 2.5 L/min of hydrogen, which resulted in a 20.12% increase in brake thermal efficiency (BTE) and a 27.57% reduction in fuel consumption compared to biodiesel. The addition of hydrogen gas has a positive impact on exhaust emissions (HC, CO2, and smoke opacity), but has a negative impact on NO emissions. At elevated loads of 2.5 lpm hydrogen flow, emissions measured were 40.00 ppm, 0.04%, 4.20%, and 44.20%, respectively, alongside a 45.72% increase in NO emissions. Including hydrogen gas improves the diesel engines running on biodiesel's performance and exhaust pollutants.